2010
DOI: 10.1038/ismej.2010.123
|View full text |Cite
|
Sign up to set email alerts
|

Transmission dynamics of an emerging infectious disease in wildlife through host reproductive cycles

Abstract: Emerging infectious diseases are major threats to wildlife populations. To enhance our understanding of the dynamics of these diseases, we investigated how host reproductive behavior and seasonal temperature variation drive transmission of infections among wild hosts, using the model system of cyprinid herpesvirus 3 (CyHV-3) disease in common carp. Our main findings were as follows: (1) a seroprevalence survey showed that CyHV-3 infection occurred mostly in adult hosts, (2) a quantitative assay for CyHV-3 in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(46 citation statements)
references
References 31 publications
2
44
0
Order By: Relevance
“…This is in concordance with the many empirical examples where infectious diseases emerge in the season when the hosts aggregate (Altizer et al 2006). In case of CyHV-3 disease in Lake Biwa, the virus is suggested to transmit among adult carps by contact through group mating in the limited breeding habitats where the adult density is much higher than that in other seasons (Uchii et al 2009(Uchii et al , 2010. We consider that the outbreak of disease may occur within one breeding season, starting from a few infected individuals, where there is no recruitment of adult individuals.…”
Section: Application To Cyhv-3 In Lake Biwasupporting
confidence: 65%
See 1 more Smart Citation
“…This is in concordance with the many empirical examples where infectious diseases emerge in the season when the hosts aggregate (Altizer et al 2006). In case of CyHV-3 disease in Lake Biwa, the virus is suggested to transmit among adult carps by contact through group mating in the limited breeding habitats where the adult density is much higher than that in other seasons (Uchii et al 2009(Uchii et al , 2010. We consider that the outbreak of disease may occur within one breeding season, starting from a few infected individuals, where there is no recruitment of adult individuals.…”
Section: Application To Cyhv-3 In Lake Biwasupporting
confidence: 65%
“…One of the reasons for such a major outbreak is possibly attributed to the high infection rate of CyHV-3 due to the high density of adult carps. Especially, the decrease of breeding habitats in the lakeshore due to lakeshore protection works and water level control (Biwako Handbook Editors Commission 2007) could accelerate the infection because the latest study suggested that CyHV-3 transmits among adult carps in the breeding habitats while group mating (Uchii et al 2009(Uchii et al , 2010. The phenomenon of disease transmission in the spawning phase has also been reported in salmonoid fishes (Nylund et al 2003).…”
Section: Introductionmentioning
confidence: 91%
“…In addition, CyHV-3 has been detected 3-4 years after the outbreak (Minamoto et al, 2009;Honjo et al, 2010). Uchii et al (2011) concluded that CyHV-3 disease spreads among the breeding habitat of carp.…”
Section: Discussionmentioning
confidence: 97%
“…In the experiments described by Bergmann & Kempter (2011), the virus load increased to 10 3 copies in individual carp 3 to 7 d after a stress event at a water temperature of 20°C. In a carp population from the Japanese Lake Biwa, high CyHV-3 concentrations were primarily detected during reproduction in the spring (Uchii et al 2010). Table 4.…”
Section: Discussionmentioning
confidence: 99%
“…n.t. : not tested Then a high virus load coincided with a high testosterone level in the carp population, which has been reported to suppress immune functions in common carp (cited from Uchii et al 2010). In the current study, the stress response to the harvesting process could not be investigated.…”
Section: Discussionmentioning
confidence: 99%